KEWARISAN JANDA DAN DUDA MENURUT HUKUM ADAT KAILI DITINJAU DARI FIQH MAWARIS - Bahdar Bahdar (ISTIQRA, 2017)
This study examines aspects of customary law of inheritance law Kailinamely the transfer of ownership of property to the beneficiary in terms of fiqh Mawaris. The issues raised in this research is how the process of widows and widowers inheritance under customary law Kaili and how much a part of each. Through this research note that the procedure divisioninheritance to widows and widowers under customary law Kaili depend on the condition of divorce and the death of a spouse Treasures that made heritage is a treasure together instead of the default property of giving parents or property acquired before they were married. If your wife or husband killed deliberately, the killer was not given inheritance, If killed accidentally or in self-defense, the property is divided in two. If a husband or wife asks for a divorce with no reason justified customs then divorces were not given the inheritance.If the divorce is justified by customary law the property is divided into two. The results of this study indicatethat procedure inheritance of widows and widowers according to customary law in line with the provisions of fiqhMawaris. The equation of which can be seen on the property which is used as inheritance is a joint property and killers are not given the inheritance of the people he killed. Kaili according to customary law in accordance with fiqh Mawaris.Conformity can be seen in three ways. Killer did not get the estate of the person who killed. Inheritance and divorce occurred because of the death of the husband and wife. Treasure that heritage is used as a common property that are cultivated husband and wife